Generation of Synchronous Unpredictable Oscillations by Coupled Hopfield Neural Networks - Fen, Mehmet Onur; Fen, Fatma Tokmak (Journal of Applied Nonlinear Dynamics, 2026)
A criterion based on generalized synchronization is provided for the extension of unpredictable oscillations among coupled Hopfield neural networks (HNNs). It is shown that if the drive network possesses an unpredictable oscillation, then the same is true for the response network provided that they are synchronized in the generalized sense. Extension of unpredictability in coupled 4D HNNs is exemplified with simulations. The auxiliary system approach and conditional Lyapunov exponents are utilized to demonstrate the presence of synchronization.